Estimation of Ductility Demand in RC Buildings Induced by Repeated Earthquakes - Ade Faisal, Ph.D (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
Current design practice considers the use of single event of earthquake. In fact, seismic hazard is a multi events earthquake or the so-called repeated earthquakes. Consequently, the structural behavior under repeated earthquakes is not clearly understood. Therefore, the present study focused on the estimation of ductility demands in reinforced concrete (RC) buildings affected by repeated near-field earthquake having forward directivity effect (FDE). A comprehensive assessment was conducted using generic frames with 4 types of fundamental period. A model having behavior factor (or force reduction factor) of 1.5, 2, 4, and 6.0, and plastic hinge at member ends with 3 types of plastic rotation capacity was assumed. The buildings were assumed to be situated on a stiff soil in the high seismic zone in Europe. This study shows that, on average, the amplification ratio of roof ductility demand due to repeated earthquakes reached to 1.5 and 1.7 for double and triple events of repeated earthquakes, respectively. The present study has also established the empirical relationships of ductility demands of RC building with the fundamental period, behavior factor, ratio of global post-yield stiffness to elastic stiffness, and ratio of story ductility to global ductility capacities to predict the amplification ratios of ductility demand due to repeated earthquakes.